KOMUNIKASI KEBIJAKAN DALAM PELAKSANAAN DANA DESA DI DESA WATUDAMBO II KECAMATAN KAUDITAN KABUPATEN MINAHASA UTARA - WUMU, ABDUL MUNIF; DENGO, SALMIN; LONDA, VERY (Sam Ratulangi University, 2022)
The purpose of this study is to find out how policy communications in village funding in the Desa WatudamboII district north Minahasa district.Research uses a descriptive - qualitative approach. The policy is based onthree key aspects of public policy communication, of transmission, clarity and consistency. The researchinformant is the village chief and village device, the chairman and member of the village council, the chairmanof the village PKK, the group representative, and the village public figure, a total of 8 informers. Datacollection uses the interview guidelines, while the analysis techniques used are interactive model analysis fromMiles and Hubernann.Based on the results of research drawn to conclusion: 1. The policy communications inmanaging village funds from the